CHCHD2 and CHCHD10-related neurodegeneration: molecular pathogenesis and the path to precision therapy. (26th April 2023) - Shammas, Mario K.; Huang, Tzu-Hsiang; Narendra, Derek P.
Abstract : In the last decade, dominant mutations in the mitochondrial protein CHCHD10 (p.R15L and p.S59L) and its paralog CHCHD2 (p.T61I) were shown to cause familial amyotrophic lateral sclerosis (ALS) and Parkinson's disease (PD), respectively, with phenotypes that often resemble the idiopathic forms of the diseases. Different mutations in CHCHD10 cause additional neuromuscular disorders, including the lower motor neuron disease Spinal Muscular Atrophy Jokela type (SMAJ) (p.G66V) and autosomal dominant isolated mitochondrial myopathy (IMMD) (p.G58R). Modeling these disorders is revealing how mitochondrial dysfunction may drive ALS and PD pathogenesis by a gain of function mechanism, driven by protein misfolding of CHCHD2 and CHCHD10 into toxic species. It is also laying the groundwork for precision therapy of CHCHD2/CHCHD10-related neurodegeneration. In this review, we address the normal function of CHCHD2 and CHCHD10, the mechanisms of their disease pathogenesis, the strong genotype–phenotype correlations that have emerged for CHCHD10, and potential therapeutic strategies for these disorders.